Comparison of flax seeds extract and fenugreek seed extract rinse against streptococcus mutans colonies - Syeda Amber Zaidi, Faiza Quraishi, Sarwath Fatimee, Lubna Farooq, Hina Masood, Tajwar Sultana (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To compare flax seeds extract and fenugreek seed extractrinse against streptococcus mutans colonies Study setting: The bench work of this preclinical experimental study was carried out at Baqai Medical and Dental College Karachi., from December 2021 to January 2022. Materials and Methods: It was a preclinical experimental study. Participants were divided into 4 groups randomization was performed in allocating the groups of participants. Film of plaque from labial surface of teeth of study participants was collected on sterile strips before and after the 2 hours of intervention. The extract preparation of both the plants and culture of S. mutantcolonies were performed as per standard protocol. The extract was diluted at 1:4 for rinsing and study participants were given the rinses according to their groups. Data was analyzed by SPSS v. 22 Results: The growth of colonies was calculated on growth media plates in samples prior to rinsing and samples that were taken after the rinsing. The pre and post samples showed significant (p-value <0.05) decrease in number of colonies in positive control group (conventional rinse), flax seed extract group and fenugreek seed extract group as shown in table 1. The intra group comparison of negative and positive control showed significant difference in number of colonies and same was observed with the both the extract rinses. However, the positive control and flax seed extract and fenugreek seed extract comparison was insignificant that highlighted the equal potential of herbal extracts in reducing the streptococcus mutans colonies. Conclusion: Flax seeds extract and fenugreek seed extract mouth rinses reduced the number of colonies equally as that of commercially available mouth rinse.